2017
DOI: 10.1021/jacs.7b08693
|View full text |Cite
|
Sign up to set email alerts
|

Synergic “Click” Boronate/Thiosemicarbazone System for Fast and Irreversible Bioorthogonal Conjugation in Live Cells

Abstract: Fast, high-yielding, and selective bioorthogonal "click" reactions employing nontoxic reagents are in high demand for their great utility in the conjugation of biomolecules in live cells. Although a number of click reactions were developed for this purpose, many are associated with drawbacks and limitations that justify the development of alternative systems for both single- or dual-labeling applications. Recent reports have highlighted the potential of boronic ester formation as a bioorthogonal click reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 38 publications
0
49
0
3
Order By: Relevance
“…14B). 126 This new system is similar to the previous one but, through the introduction of an additional hydrazone ligation, the reaction became irreversible. This click type reaction was successfully applied to site selective protein labelling on mammalian HEK293T cells.…”
Section: Boronate Estersmentioning
confidence: 90%
“…14B). 126 This new system is similar to the previous one but, through the introduction of an additional hydrazone ligation, the reaction became irreversible. This click type reaction was successfully applied to site selective protein labelling on mammalian HEK293T cells.…”
Section: Boronate Estersmentioning
confidence: 90%
“…31 They also showed that the 2-acetylphenylboronate unit forms more stable bonds with hydrazide, hydrazine and aminooxy functionalities, 32 indicating that 2-acetylphenylboronic acid would be potentially applicable as a novel reaction handle for bioorthogonal click chemistry. 33…”
Section: •1 Lysinementioning
confidence: 99%
“…[63] Die initiale Boronatbildung ist nachweislich essenziell fürd ie intramolekulare Thiosemicarbazonbildung und liefert ein mittelgroßes Ringaddukt. Dies kçnnte ihre Anwendung bei der Abbildung lebender Zellen erschweren, da das Boronataddukt unerwünschte Spaltungsreaktionen eingehen kçnnte,w ährend überschüssiges Reagenz in einem Waschschritt entfernt wird.…”
Section: Irreversible Synergetische Boronat-/semicarbazonbildungunclassified